The effectiveness of post-mining land rehabilitation policy in realizing environmental sustainability: Lessons from Sukageuri View, Kuningan, West Java - Akhmaddhian, Suwari; Supartono, Toto; Anugrah, Dikha; Hidayat, Sarip; Budiman, Haris; Yuhandra, Erga; Setiawan, Wawan (Journal of Degraded and Mining Lands Management, 2023)
The effective management of natural resources is critical in achieving environmental sustainability, and it requires a careful balance of ecological and economic interests. Therefore, this study analyzed the effectiveness of village government policy in managing post-mining land for environmental sustainability using a non-doctrinal legal approach. Primary data were collected through interviews and observations, while secondary data came from regulations, scientific journals, and papers related to post-mining land rehabilitation governance. The study was conducted in Sukageuri View, Kuningan Regency. The study found that the policy implemented by the Cisantana Village Government in managing post-mining land through the establishment of the Village-Owned Enterprise (VOE) in 2016 has been effective. The area, formerly known as Sukageuri View, is home to various flora and fauna species, with several businesses operating and over 114,000 visitors engaging in social activities in 2022. Additionally, the site has contributed to the village's original income and supported the work program of the Cisantana Village Government. In conclusion, the policy implemented by the Cisantana Village Government effectively balances ecological, social, and economic factors, meeting the criteria for environmental sustainability.